Análise das diretrizes da biodiversidade em programas de uso público em cinco unidades de conservação de proteção integral do estado de São Paulo - Parra, José Airton Salazar (2007)
Having seen to crescent seeks for the Protected Areas (Units of Conservation in the Brazilian Sistems) for the practice of the ecotourism and environmental education, this work looked for to identify aspects of importance to the conservation, lifting information on as the manage plans they contemplate the Program of Public Use and being analyzed the conservation of the biodiversity is considered in the elaboration and implantation of this program. Information were analyzed obtained through applied questionnaires to the managers of twenty-six Protected Areas of Integral Protection of the state of São Paulo (Brazil). It was verified that is important to define and to monitor impact indicators to subsidize the definition of programs of public use, because these activities can bring impacts to the Protected Areas. The variety of existent ecosystems in the Protected Areas and the interface of these with several remainders propitiates conditions for larger diversity. Several units shelter endemic species, threatened of extinction, besides they be landing points, feeding and reproduction of migratory species. This way, the ecological relationships they should be contemplated in plans to avoid the negative effects of the public visitation.